RITUAL COMMUNICATION TEPUNG TAWAR IN TRADITIONAL BATAK WEDDING IN KAMPUNG PAJAK VILLAGE NORTH LABUHANBATU REGENCY (ISLAMIC COMMUNICATION PERSPECTIVE): culture, communication ritual, tradition - Aritonang, Ray Syam Piqri; Yusriani Simamora, Irma (Program Studi Komunikasi dan Penyiaran Islam Fakultas Dakwah Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan, 2023)
Wedding receptions in Indonesia have a lot of diversity in every ethnic group. Various cultures and traditions color each region from various parts of the Province. The diversity of customs, cultures and traditions is basically a wealth for the Indonesian people and should also be preserved by every generation. In this research, several discussions regarding the history and interesting facts about the Tap Flour Ritual Tradition in Batak Traditional Marriages in Kampung Tax Village, North Labuhanbatu Regency, will be revealed. The aim of this research is to extract several points of communication contained in this tradition. Thus, it has become the duty of the government to participate in and preserve every positive tradition passed down by the ancestors of the archipelago.